Characterisation of osteomyelitis microbiome using specific growth media - Ali, Fatimah Maryam; Ismail, Mohd Faisal; Mohktar, Munirah; Rismayuddin, Alia Risma; Yusof, Mohd Nazri; Arzmi, Mohd Hafiz (IIUM Press, 2019)
Osteomyelitis is an inflammation of the bone caused by microbial infection. The objective of the study is to characterise the microbiome from osteomyelitis with the hypothesis that osteomyelitis is induced by polymicrobial infection. To identify the microbiome, sample was initially isolated from pin site of ortophaedic patients with osteomyelitis using sterile swab. Following that, the sample was inoculated into nutrient broth and incubated at 37° C for 24 h aerobically. Later, the sample was cultured on CHROMagar, mitis salivarius agar (MSA) and lactobacillus specific agar (LSA) for identification of Candida species, Streptococcus species and Lactobacillus species, respectively. Gram-staining was conducted to identify its phenotype under light microscope. Finally, disc diffusion test was conducted on each isolate to assess its sensitivity towards nystatin, amphotericin B, gentamicin and tetracycline. Based on the study, only Candida albicans and Streptococcus species were identified. Candida albicans and Streptococcus species were isolated from the sample with C. albicans exhibited resistance to amphotericin B, gentamicin and tetracycline while Streptococcus species were resistance to nystatin, amphotericin B and tetracyclin. In conclusion, osteomyelitis is induced by polymicrobial infection, with the microbial isolates possess various susceptibility towards common antimicrobial agents.